Implementation of online learning for statistics subject in grade VIII students with a scientific approach - Muna, Mila Zamilatun; Miftahudin, Rifqi Aulia (CV. Pustaka Literasi Ilmiah, 2023)
Scientific approach is a learning approach that uses problem in everyday life. The first scientific learning step is observing, the second is asking questions, the third is gathering information, the fourth is reasoning or trying, and the fifth is communicating. The method of this research is descriptive qualitative research which aims to describe the process of implementing online learning statistics material for grade VIII junior High school students with a scientific approach. Based on the results of the research, it shows that the implementation of learning is in accordance with the scenarios that have been prepared in lesson plan and worksheet.